THE ROLE OF EARLY MORNING WORSHIP IN DEVELOPING SPIRITUAL INTELLIGENCE AMONG THIRD-YEAR FEMALE STUDENTS AT AKPER BETHESDA SERUKAM - Noldy Gosal (PT. Radja Intercontinental Publishing, 2026)
Spiritual intelligence refers to an individual's ability to understand the meaning of life, cultivate a relationship with God, and apply moral values in everyday conduct. Bible reading as a component of early morning worship is believed to support students' spiritual development. This study aimed to explore the role of Bible reading during early morning worship in enhancing the spiritual intelligence of Class XXI students residing at the Women's Dormitory of Akper Bethesda Serukam. A qualitative research design with a descriptive phenomenological approach was employed. Six participants were selected through purposive sampling. Data were gathered via in-depth interviews and analyzed using the Colaizzi method. Four main themes emerged from the findings: (1) Bible reading during early morning worship strengthens students' spirituality; (2) Bible reading shapes positive character; (3) laziness and excessive smartphone use constitute major barriers to Bible reading; and (4) Bible reading encourages attitudes of love, forgiveness, and prayer for others. The results indicate that regular Bible reading positively contributes to spiritual intelligence through faith growth, character transformation, and the strengthening of social relationships. It is concluded that Bible reading during early morning worship plays a significant role in fostering students' spiritual intelligence. Accordingly, spiritual formation programs should be continually developed to sustain and enhance students' spiritual growth.